Occurrence of Cryptosporidium spp. and Giardia spp. in pigs at weaning - Matos, Denise Junqueira [UNESP]; Meireles, Marcelo Vasconcelos [UNESP]; Coelho, Willian Marinho Dourado [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (Universidade Estadual de Londrina, 2016)
Cryptosporidium spp. and Giardia spp. are parasites and have been reported in many species of mammals, including humans. The goal of this research was to investigate the occurrence of Cryptosporidium spp. and Giardia spp. in 45-days-old pigs. Fecal samples of 107 pigs were collected at three alternate days in piggeries in Araçatuba, São Paulo State, Brazil. Cryptosporidium oocysts were observed in 4.7% (5/107) of animals by Kinyoun acid-fast stain method and cysts of Giardia spp. were observed in 1.9% (2/107) of the animals by the method of Faust. Of all animals, 85 presented feces with normal consistency and 22 showed diarrhea in at least one collection. Two diarrheic samples showed positivity for both Cryptosporidium spp. and Giardia spp. From these results it is possible to infer that the occurrence of Cryptosporidium and Giardia was low because of the good management practices and both protozoa were not associated the presence of symptoms.
Keywords: Cysts; Diarrhea; Feces; Oocysts; Piggery; Protozoonosis